The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/ja0506509
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Nickel-Catalyzed Negishi Cross-Couplings of Secondary α-Bromo Amides with Organozinc Reagents

Abstract: A Ni/Pybox catalyst achieves the asymmetric cross-coupling of secondary alpha-bromo amides with organozinc reagents. The process tolerates a variety of functional groups and affords the desired product in good yield and in high enantiomeric excess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
120
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(128 citation statements)
references
References 6 publications
(8 reference statements)
2
120
0
6
Order By: Relevance
“…Die durch NiCl 2 und iPr-Pybox katalysierten Umsetzungen von racemischen a-Bromamiden führten mit guten Ausbeuten und hohen Enantiomerenüber-schüssen (ee) zu zahlreichen funktionalisierten a-substituierten Amiden (Schema 3). [11] Die Reaktionen erfordern keinerlei besondere Vorkehrungen und laufen an der Luft ab. An diesen Kupplungen nehmen sowohl nichtfunktionalisierte als auch funktionalisierte Organozinkreagentien teil, einschließlich jener mit Olefin-, Benzylether-, Acetal-, Imid-und Nitrileinheiten.…”
Section: Nickelkatalysierte Reaktionenunclassified
“…Die durch NiCl 2 und iPr-Pybox katalysierten Umsetzungen von racemischen a-Bromamiden führten mit guten Ausbeuten und hohen Enantiomerenüber-schüssen (ee) zu zahlreichen funktionalisierten a-substituierten Amiden (Schema 3). [11] Die Reaktionen erfordern keinerlei besondere Vorkehrungen und laufen an der Luft ab. An diesen Kupplungen nehmen sowohl nichtfunktionalisierte als auch funktionalisierte Organozinkreagentien teil, einschließlich jener mit Olefin-, Benzylether-, Acetal-, Imid-und Nitrileinheiten.…”
Section: Nickelkatalysierte Reaktionenunclassified
“…The reaction conditions were optimized carefully, and it was found that the optimal combination of a solvent, nickel precursor, and additive differed for each class of substrate. [6] Interestingly, in each of these studies, nickel-pybox complexes formed in situ were found to be the most active and most selective catalysts; furthermore, donor solvents, such as 1,3-dimethyl-2-imidazolidinone (DMI), N,N-dimethylacetamide (DMA), and N,Ndimethylformamide (DMF), were found to be crucial. The exact mechanism of these transformations still remains to be elucidated.…”
mentioning
confidence: 97%
“…Thus, the rate of reductive elimination is increased relative to that of undesired b-hydride elimination. Recently, Fu and co-workers developed a number of impressive highly enantioselective nickelcatalyzed Negishi, [6] Hiyama, [7] and Suzuki-Miyaura [8] crosscoupling reactions of secondary alkyl halides. The last of these methods is the only asymmetric cross-coupling described to date in which non-activated secondary alkyl halides can be used and thus paves the way for exciting future developments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Condensed ring substrates 1 f and 1 g also gave the desired products 2 f and 2 g in high yields and with 96 % ee and 92 % ee, respectively (Table 2, entries 6 and 7). The electronrich substituents on 1 h-1 j underwent the IOM addition and decarboxylation processes to yield the enantiomeric adducts (2 h-2 j) in excellent yields and with ee values in the range 84-93 % ee ( Table 2, entries [8][9][10]. The aliphatic substrate 1 k was also found to be suitable, affording chromanone 2 k in 90 % yield and with 85 % ee (Table 2, entry 11).…”
mentioning
confidence: 98%